Efektifitas Penggunaan Media Kemistripoli Berbantuan Apkomacro Pada Pembelajaran Kimia - Farizal, Farizal (SCAD Independent, 2024)
Chemistripoli is a chemistry learning medium that modifies the rules and tools of the monopoly game. This research began with designing media and applications for calculating the mole concept (Apkomacro) based on macro language (Visual Basic of Application for Microsoft Excel), creating media along with usage guidelines, and applying chemistry in learning. This research aims to apply Kemistripoli and Apkomacro media and determine the effectiveness of using Kemistripoli in chemistry learning on the subject of the mole concept in class X.1 of SMA Negeri 1 Girimulya, especially regarding learning activities, student responses and student learning outcomes. Chemistry is said to be effective in learning if it meets the criteria for student activeness in the teaching and learning process to be in the good criteria (19 – 24), the percentage of students who have a positive response is ≥ 75.1%, classically 90% of students get a score ≥ 65 and classically 85% of students get a score ≥ KKM Chemistry in Class X SMA Negeri 1 Girimulya (≥70). Data collection was obtained using student observation sheets, tests and student response questionnaires. Based on the results of the research conducted, it is known that the use of Kemistripoli for learning chemistry, the main topic of the mole concept, is very effective. Proven by observation data (score 23, good criteria), student questionnaire responses (positive response (85.33%) and student learning outcomes (96.67% score ≥ 65 and 90% score ≥ KKM).